(untitled) (Annals of Medical Research, 2021)
Aim: In dental trauma injuries, proper diagnosis and initial intervention are important in terms of prognosis. The aim of this study was to determine the knowledge levels and attitudes of pediatricians about traumatic dental injuries.Materials and Methods: There were 141 specialist pediatrician and assistant pediatrician working in universities or public hospitals who participated in this cross-sectional survey study. An electronic questionnaire was developed by the authors using Google Forms. The questionnaire consists of three parts and contains 22 questions in total. In the first part, the personal information of the physicians is recorded. The second part consists of questions regarding their knowledge and attitudes about dental trauma. The third part involves photos of the two cases we took from our clinical archive, which include a crown fracture and a case of avulsion dental trauma.Results: Almost half (44.7%) of the pediatricians had experienced traumatic dental injuries at least once. Only one-third (33.3%) of the respondents had heard the term avulsion. In the first case scenario, most of the participants (81.4%) stated that the broken tooth part should be saved. In the second case scenario, just over a third of the respondents (36.9%) said that in the case of avulsion, they would refer their patients to the dentist immediately, without doing anything. As the best storage medium, saline was answered most often (20.5%), followed by sterile sponge (19.1%), clean napkin (12.1%), and milk (11.3%). A statistically significant difference was found between procedures (recommended vs. non-recommended) for case 1 and case 2, according to professional experience (p 0.05).Conclusion: Knowledge of pediatricians about dental trauma was found to be insufficient. Pediatricians should be trained on dental trauma during their specialization or medical education, and their awareness and willingness to manage it should be increased.